KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP KELAS VIII PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DENGAN PENDEKATAN OPEN ENDED - Nuni Mulyowati; Muhammad Afrilianto; Euis Eti Rohaeti (IKIP Siliwangi, 2018)
The objective of this research is to analyze theimprovement of problem solving ability from students at VIII grade on material of two variables linear equationssystem thtough open ended approach. This research uses Classroom Action Reserch. The method of the research is descriptive. The research is conducted to VIII H grade student of SMP Negeri 9 in academic year 2017/ 2018 which consist of 40 students. The instrument is the testof students’ mathematical problem solving ability, cycle test I and II after giving action. The result aspectof this research shows that the aspect of students’ mathematical problemsolving ability increased, it can be seen from the result of the test, many studentsachive above beverage score (KKM).Bsed on indicator, it concludes that students’ problem solving ability at VIII H grade of SMP Negeri 9on material of two variables linear equations system can be improved through open ended approach